Strategic Energy Resources – Tool of Political and Energy Pressure - Daniel N. Fita; Sorina D. Stanila; Dragos Pasculescu; Teodora Lazar; Florin G. Popescu; Florin Grecu-Muresan (Recent Trends in Arts and Social Studies Vol. 1, 2023)
The aim of the paper is to demonstrate theoretically and practically that energy in all its forms (resources, coal, oil, natural gas, uranium or electricity) can be a reason for cooperation but also for confrontation with connotations often military, generating wars that seriously damage all social environments and thus global welfare. The authors propose to suggest some actions that can generate stability and energy well-being, factors that cause world peace. At present, the geostrategic, geopolitical and geomilitary positioning of a state, regardless of its membership and role in various economic-military unions or blocs, is no longer based solely on its military power, but rather on its energy, economic, information and especially technological domination. The emergence and increasing development of energy disputes and conflicts with possible military escalation and the strong desire of the major world economic powers (USA, Russia, EU, China, India, etc.) to have control and world power, makes energy resources (coal, oil and natural gas) to be used by their holders as a tool of political pressure for profit and blackmail. Lack of energy energy resources can cause energy instability that automatically leads to national insecurity and with possible European or global repercussions, by the fact that all sectors of an economy depend on energy resources, which generate energy security and welfare for that state.